1968 in Canada : a year and its legacies - Hawes, Michael K., 1954-; Holman, Andrew C. (Andrew Carl), 1965-; Kirkey, Christopher John, 1962- (Mercury series. History paper., 2021)
"The year 1968 in Canada was an extraordinary one, unlike any other in its frenetic pace of activities and their consequences for the development of a new national consciousness among Canadians. It was a year when decisions and actions, both in Canada and outside its borders, were thick and contentious, and whose effects were momentous and far-reaching. It saw the rise of Trudeaumania and the birth of the Parti Québécois; the articulation of the new nationalism in English Canada and an alternative vision for Indigenous rights and governance; a series of public hearings in the Royal Commission on the Status of Women; the establishment of the Canadian Radio and Television Commission, nation-wide Medicare and CanLit; and a striving for both a new relationship with the United States and a more independent foreign policy everywhere else. And more. Virtually no segment of Canadian life was untouched by both the turmoil and the promise of generational change."--